The Influence of E-Commerce, Product Prices and Product Design on Purchasing Decisions in Souvenir Shop Tauko Medan - Nanda, Nurul Nadzfah (Budapest International Research and Critics University, 2019)
Purchasing decisions made by consumers in Tauko Medan have decreased, this can be seen in the number of sales in Tauko Medan. The purpose of this study was to determine and analyze the influence of e-commerce, product prices and product design on purchasing decisions in Tauko Medan. Data collection in this study was carried out through a survey approach by distributing questionnaires. The population of this research were 399 people of Tauko Medan customers who had madeÂ online purchases. The number of research samples were 80 people. The method of data analysis used descriptive analysis and statistical analysis of multiple linear regression. Research results showed that simultaneously e-commerce, product prices and product design have a positive and significant effect on purchasing decisions in Tauko Medan. Partially e-commerce has a positive and significant effect on purchasing decisions in Tauko Medan. Likewise, the price of products partially had a positive and significant effect on purchasing decisions in Tauko Medan. Partially product design had a positive and significant effect on purchasing decisions in Tauko Medan. Of the three variables e-commerce was dominant in influencing purchasing decisions in Tauko Medan.